1978
DOI: 10.1007/bf00445613
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII activity and factor VIII related antigen in newborns

Abstract: Factor VIII procoagulant activity and factor VIII related antigen were examined in 20 full-term and preterm newborn infants during the first days of life. The control group involved 15 adults volunteers. Factor VIII activity was estimated by a one-stage test and factor VIII related antigen was determined by immunelectrophoresis according to Laurell, using our own rabbit antiserum. The following results were obtained:--Factor VIII activity during the first 3 days of life did not differ from the normal range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The elevated factor VIII:C and vWFAg levels in maternal blood at the time of childbirth have been ascribed to the extreme stress of labor, 9,10 since these levels decrease to normal adult values in the first three days after delivery. 12,28 This study, which employed chromogenic microanalytic techniques, has confirmed previous reports of a significant reduction (35-45%) in the levels of antithrombin III, plasminogen, 2,4,7,15,31 and protein C 7,13 in neonates compared with adults; no such differences were noted in the levels of alpha2-antiplasmin. Recent evidence has also shown that fetal and adult antithrombin possess the same molecular weight, charge, and electrophoretic migration pattern, 16,30 and therefore newborns display a quantitative and not qualitative deficiency of antithrombin.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The elevated factor VIII:C and vWFAg levels in maternal blood at the time of childbirth have been ascribed to the extreme stress of labor, 9,10 since these levels decrease to normal adult values in the first three days after delivery. 12,28 This study, which employed chromogenic microanalytic techniques, has confirmed previous reports of a significant reduction (35-45%) in the levels of antithrombin III, plasminogen, 2,4,7,15,31 and protein C 7,13 in neonates compared with adults; no such differences were noted in the levels of alpha2-antiplasmin. Recent evidence has also shown that fetal and adult antithrombin possess the same molecular weight, charge, and electrophoretic migration pattern, 16,30 and therefore newborns display a quantitative and not qualitative deficiency of antithrombin.…”
Section: Discussionsupporting
confidence: 87%
“…1,3,13,28,29 Previous studies on the levels of factor VIII activities (factor VIII:C, vWFAg, and ristocetin cofactor) in the newborn have yielded widely contrasting results. While some authors have found neonatal factor VIII :C levels to be within the normal adult range, 7,12 others have found factor VIII:C and vWFAg to show higher values in newborns than adults. 9 We found factor VIII:C levels in neonates were at the lower end of the adult normal range, but the calculated mean is significantly lower in neonates than adults.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The finding of high levels of factor VHI-related antigen (VIII R:Ag) in the absolute sense and/or in connection with a relatively lower VIII:C level in newborns, resulting in an abnormally high ratio of VIII R:Ag over VIII:C, has lately aroused considerable interest in the literature (1,4,5). In healthy full-term newborns VIII R:Ag at birth is reported to be 1.69 U/ml (n = 33) (5) and 1.20 U/ml (n = 55) (2); in a mixed group of full-term (n = 14) and low birth weight (n = 6) newborns, VIII R:Ag is reported to be 1.82 U/ml on the average (4).…”
Section: Introductionmentioning
confidence: 99%